Questionário do Comportamento Alimentar da Criança (CEBQ) - Viana, Victor (2011)
In this paper the authors present de Portuguese version of the Children Eating Behaviour Questionnaire. There is an historic note about the questionnaire and an introduction to it theoretical background. Results of the Portuguese validation, Factor Analysis results, and psychometric characteristics, are presented.